Maurice Blanchot and fragmentary writing : a change of epoch - Hill, Leslie, 1949- (Continuum, 2012)
Writing in fragments is often held to be one of the most distinctive signature effects of Romantic, modern, and postmodern literature. But what is the fragment, and what may be said to be its literary, philosophical, and political significance? Few writers have explored these questions with such probing radicality and rigorous tenacity as the French writer and thinker Maurice Blanchot. For the first time in any language, this book explores in detail Blanchots own writing in fragments in order to understand the stakes of the fragmentary within philosophical and literary modernity. It attends in.